Exosomes From Human Umbilical Cord Mesenchymal Stem Cells Alleviate Oxidative Stress‐Induced POI by Regulating Autophagic Homeostasis Through the AMPK Pathway - Wanqi Chen; Qi Feng; Chan Zhang; Lu Yang; Jingyi Qi (Reproductive Medicine and Biology)
ABSTRACT Background Increased oxidative stress is a key factor in developing premature ovarian insufficiency (POI). Exosome therapy emerges as a promising cell‐free treatment. However, research into the molecular mechanisms of exosome repair in ovarian diseases is still in its infancy. By establishing models of oxidative stress in ovarian granulosa cells and POI in mice, we aim to explore whether human umbilical cord mesenchymal stem cell exosomes can repair oxidative damage in ovarian granulosa cells and mouse ovaries, as well as identify potential targets of action. Our goal is to provide new ideas and methods for the clinical application of exosomes and the early prevention and treatment of POI. Methods Hydrogen peroxide (H2O2) (200 μM, 2 h) and D‐galactose (D‐gal) (200 mg/kg, 56 days) were used to induce oxidative stress in ovarian granulosa cells and mice, respectively. Subsequently, exosomes were added to the injury model to validate the mechanism of exosome repair of oxidative damage. We evaluated senescence indicators, AMPK activation, and autophagy. Result Through the execution of in vivo and in vitro experiments, it was observed that the activation of the AMP‐activated protein kinase (AMPK) pathway is induced by exosome intervention, leading to a reduction in the accumulation of autophagic vesicles and the restoration of the patency of autophagic flow. This, in turn, results in the repair of oxidative stress‐induced damage and the enhancement of the function of damaged cells and ovaries. Conclusion Our findings indicate that exosomes derived from human umbilical cord stem cells have the beneficial effect of ameliorating oxidative stress‐induced POI by activating AMPK and regulating autophagic homeostasis.